Stability and Performance of Physically Immobilized Ionic Liquids for Mercury Adsorption from a Gas Stream - Abbas, T. (American Chemical Society, 2015)
Solid-supported ionic liquids (ILs) have recently received attention as a potential effective technology for mercury removal from a gas stream. However, the leaching of ILs from the solid support has not been investigated in detail. In the present study, the stability of 1-butyl-3-methylimidazolium chloride (BmimCl) impregnated on silica and activated carbon was evaluated during elemental mercury removal (Hg0) from a gas stream. Silica- and carbon-supported BmimCl-based adsorbents were characterized before and after Hg0 adsorption by using Fourier transform infrared spectroscopy, Brunauer-Emmett-Teller surface area analysis, field-emission scanning electron microscopy, energy-dispersive X-ray spectroscopy, and thermal gravimetric analysis. The carbon-supported adsorbent showed better stability (no leaching of ILs) compared to the silica-supported adsorbent because of the availability of substantial micropores. The lower stability of silica-supported ILs is attributed to the presence of mesopores on silica support, which holds BmimCl ineffectively in a gas flow of a high concentration of Hg0 (15 ppm). The activated carbon-supported ILs, especially in a powdered form, showed higher adsorption efficiency of Hg0 from a gas stream. The adsorption capacity of powdered carbon-supported BmimCl was 21 mg/g in 68 h of continuous adsorption. Â© 2015 American Chemical Society.